Comparative Effect of Two Fermented Bioles on the Morphological Growth of Lettuce (Lactuca sativa) Cultivated in Pots - Cardenas Gutierrez, Liana; Tirado Zavaleta, Marvin; Mostacero Molina, Bill; Del Castillo Sagastegui, Mariano (LACCEI, 2025)
The main objective of this research was to comparatively evaluate the effect of two types of fermented bioles on the morphological growth characteristics of lettuce (Lactuca sativa) cultivated in pots. The bioles were prepared using different microorganisms for anaerobic fermentation. After a 120-day fermentation period, a 5% foliar fertilizer solution was applied in three treatments: control (T0), LEVA biol (T1), and BACID biol (T2). The distribution followed a completely randomized block design. Plant height, number of leaves, and leaf diameter were evaluated. After 14 days, treatments T1 and T2 showed a 10% and 11% increase in plant height, respectively, compared to T0. On day 21, T2 showed a noticeable increase in the number of leaves. Additionally, on day 14, leaf diameter increased by 5% and 7% in T1 and T2, respectively, compared to T0. These results support the positive effect of bioles on the growth of lettuce in pots. This research contributes to the scientific community by promoting the development of environmentally friendly technologies.